EFFECT QUIXALUD ADDITTON ON FOOD PREFERENCE AND RESISTANCE FROM DEGRADATION - Izzati, Munifatul (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT---We  investigate  the  effect  of  quixalud  on  food  preference  and  resistance  from degradation.  Quixalud  was  choosen  because  of  its antimicrobial  properties  but it  is not an antibiotic.  The aim of this research  is to  evaluate  the effect of  quixalud addition on food preference  by tiger shrimp and its resistant from degradation.  The experiment  was designed  using Factorial with  two treatments:  quixalud concentration  and soaking  period.  We used  three  concentration  of quixalud:  30 ppm 60 ppm and  90 ppm.  Each  concentration  were soaked  at  difference  period  of time, which were:24  hours,  48 hours  and  72 hours.  Food  preference  and  resistance from  degradation were monitored. Results indicated that  there was no  different  of  shrimp  food  preference between  quixalud feed and controls or  feed without quixalud.  However,  there was a tendency  that shrimp preferred  feed  with 60 ppm of quixalud.  Quixalud  has  no effect  on  the  remaining  solid  feed. It seem  likely that the remaining solid feed  is mainly affected by the strength  of binder rather  than  the presence  of an antibacterial compound,  such  as  quixalud.Keywords  : quixalud, food preference, resistance, degradation.Permalink : http://ejournal.undip.ac.id/index.php/sm/article/view/3114